Metabolomics and proteomics insights into hepatic responses of weaned piglets to dietary Spirulina inclusion and lysozyme supplementation - Cátia Falcão Martins; Manolis Matzapetakis; David M. Ribeiro; Josipa Kuleš; Anita Horvatić; Nicholas Guillemin; Peter David Eckersall; João P. B. Freire; André M. Almeida; José A. M. Prates (BMC Veterinary Research)
Abstract Background Studying the effect of dietary Spirulina and lysozyme supplementation on the metabolome and proteome of liver tissue contributes to understanding potential hepatic adaptations of piglets to these novel diets. This study aimed to understand the influence of including 10% Spirulina on the metabolome and proteome of piglet liver tissue. Three groups of 10 post-weaned piglets, housed in pairs, were fed for 28 days with one of three experimental diets: a cereal and soybean meal-based diet (Control), a base diet with 10% Spirulina (SP), and an SP diet supplemented with 0.01% lysozyme (SP + L). At the end of the trial, animals were sacrificed and liver tissue was collected. Metabolomics analysis (n = 10) was performed using NMR data analysed with PCA and PLS-DA. Proteomics analysis (n = 5) was conducted using a filter aided sample preparation (FASP) protocol and Tandem Mass Tag (TMT)-based quantitative approach with an Orbitrap mass spectrometer. Results Growth performance showed an average daily gain reduction of 9.5% and a feed conversion ratio increase of 10.6% in groups fed Spirulina compared to the control group. Metabolomic analysis revealed no significant differences among the groups and identified 60 metabolites in the liver tissue. Proteomics analysis identified 2,560 proteins, with 132, 11, and 52 differentially expressed in the Control vs. SP, Control vs. SP + L and SP vs. SP + L comparisons, respectively. This study demonstrated that Spirulina enhances liver energy conversion efficiency, detoxification and cellular secretion. It improves hepatic metabolic efficiency through alterations in fatty acid oxidation (e.g., upregulation of enzymes like fatty acid synthase and increased acetyl-CoA levels), carbohydrate catabolism (e.g., increased glucose and glucose-6-phosphate), pyruvate metabolism (e.g., higher levels of pyruvate and phosphoenolpyruvate carboxykinase), and cellular defence mechanisms (e.g., upregulation of glutathione and metallothionein). Lysozyme supplementation mitigates some adverse effects of Spirulina, bringing physiological responses closer to control levels. This includes fewer differentially expressed proteins and improved dry matter, organic matter and energy digestibility. Lysozyme also enhances coenzyme availability, skeletal myofibril assembly, actin-mediated cell contraction, tissue regeneration and development through mesenchymal migration and nucleic acid synthesis pathways. Conclusions While Spirulina inclusion had some adverse effects on growth performance, it also enhanced hepatic metabolic efficiency by improving fatty acid oxidation, carbohydrate catabolism and cellular defence mechanisms. The addition of lysozyme further improved these benefits by reducing some of the negative impacts on growth and enhancing nutrient digestibility, tissue regeneration, and overall metabolic balance. Together, Spirulina and lysozyme demonstrate potential as functional dietary components, but further optimization is needed to fully realize their benefits without compromising growth performance.